Characterization of inducible cold-active β-glucosidases from the psychrotolerant bacterium Shewanella sp. G5 isolated from a sub-Antarctic ecosystem - Cristobal, Hector Antonio (2009)
The psychrotolerant bacterium Shewanella sp. G5 was used to study differential protein expression on glucose and cellobiose as carbon sources in cold-adapted conditions. This strain was able to growth at 4 °C, but reached the maximal specific growth rate at 37 °C, exhibiting similar growing rates values with glucose (μ: 0.4 h−1) and cellobiose (μ: 0.48 h−1). However, it grew at 15 °C approximately in 30 h, with specific growing rates of 0.25 and 0.19 h−1 for cellobiose and glucose, respectively. Thus, this temperature was used to provide conditions related to the environment where the organism was originally isolated, the intestinal content of Munida subrrugosa in the Beagle Channel, Fire Land, Argentina. Cellobiose was reported as a carbon source more frequently available in marine environments close to shore, and its degradation requires the enzyme β-glucosidase. Therefore, this enzymatic activity was used as a marker of cellobiose catabolism. Zymogram analysis showed the presence of cold-adapted β-glucosidase activity bands in the cell wall as well as in the cytoplasm cell fractions. Two-dimensional gel electrophoresis of the whole protein pattern of Shewanella sp. G5 revealed 59 and 55 different spots induced by cellobiose and glucose, respectively. Identification of the quantitatively more relevant proteins suggested that different master regulation schemes are involved in response to glucose and cellobiose carbon sources. Both, physiological and proteomic analyses could show that Shewanella sp. G5 re-organizes its metabolism in response to low temperature (15 °C) with significant differences in the presence of these two carbon sources.